Systematic significance of stipe anatomy in Peninsular Malaysian Blechnum L. (Blechnaceae) species - Noraini, T.; Amirul-Aiman, A.J.; Jaman, R.; Nor-Fairuz, A.R.; Maideen, H.; Damanhuri, A.; Ruzi, A.R. (Penerbit Universiti Kebangsaan Malaysia, 2014)
A study on the stipe anatomy was conducted on six taxa of Blechnum in Peninsular Malaysia namely B. finlaysonianum, B. fraseri, B. indicum, B. melanocaulon subsp. pallen, B. orientale and B. vestitum. The objective of this study is to investigate the variations in the stipe anatomical characteristics that can be used for species identification and classification. There are five stipe anatomical characteristics found in this study that can be used to distinguish the Blechnum species. The characters are stipe outlines, patterns of sclerenchyma cell layers present under epidermal cells, presence and absence of sclerenchyma cell layer encircled the vascular bundles, number of vascular bundles, and presence of auricles on the adaxial side of stipe. Similarities found in stipe anatomical characteristics in all Blechnum species studied are the Aspidium stele type and presence of sclerenchyma cell layers underneath the epidermal layer. The diagnostic anatomical characteristics found in this study is the absence of sclerenchyma cells layer ensheathing each vascular bundles in the steles of B. finlaysonianum. Therefore, the stipe anatomical characteristics can be used in the identification of species in the genus Blechnum.